If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-4x + 9) = 165 Reorder the terms: 5(9 + -4x) = 165 (9 * 5 + -4x * 5) = 165 (45 + -20x) = 165 Solving 45 + -20x = 165 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + -20x = 165 + -45 Combine like terms: 45 + -45 = 0 0 + -20x = 165 + -45 -20x = 165 + -45 Combine like terms: 165 + -45 = 120 -20x = 120 Divide each side by '-20'. x = -6 Simplifying x = -6
| y=0(2)2 | | 3+4(7-9)*2= | | 24=3e | | 6-3x=5x-10x+5 | | 25+11/12y=47 | | 1/3(6X-2)=5 | | 43+19+(-6)= | | w-1/4=w+3/3 | | 7(5x-5)=0 | | 4y-7=-10+y | | 5(c-7)=5 | | 2x/2=105 | | 2x+4=105 | | 2(s+4)=16 | | x=35-6y | | 17*15/(17*15) | | d/2+20-13=42 | | -3(4x+4)=-12solve | | 1/3(3x) | | x+6x-8=13 | | 2125=25p+15(20-p) | | 2x-2=105 | | 4+3z-1=9z+3-4z | | 21.25=0.25p+1.5(20-p) | | -5/6/(-5/6) | | 2x+2=105 | | 5(3x-6)=10x+65 | | 3x+70=7x+40 | | -12.8/(-2) | | 5x+3=7x+1.5 | | y=0(-2)-2 | | px=90-3x |